Pengaruh Citra Merek, Kualitas Produk Dan Promosi terhadap Keputusan Pembelian Produk Proyektor Epson Di Jakarta - Dewi, Ary Susana; Elwisam, Elwisam (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2021)
Purpose The purpose of this study was to analyze the effect of brand image, product quality and promotion on purchasing decisions of Epson projectors. Methodology The data analysis technique used is multiple linear regression analysis. The sampling technique in this research is non-probability purposive sampling. The sample used in this study was 100 respondents. Findings The results showed that the variable of brand image, product quality and the promotion of positive and significant influence on purchasing decisions. The variables that have a major contribution in purchasing decisions for Epson projector products are product quality, brand image, and promotion.. Suggestion Product quality needs to be continuously improved to improve purchasing decisions.